2017
DOI: 10.1111/bjh.14645
|View full text |Cite
|
Sign up to set email alerts
|

Treating Philadelphia chromosome/BCR‐ABL1 positive patients with Glivec (Imatinib mesylate): 10 years’ experience at Patan Hospital, Nepal

Abstract: Summary The Glivec International Patient Assistance Programme makes Glivec (Imatinib mesylate) available to Philadelphia chromosome/BCR‐ABL1 positive patients with chronic myeloid leukaemia (CML) in Lower and Middle Income Countries (LMIC). We have established a large cohort of 211 CML patients who are eligible for Imatinib, in Kathmandu, Nepal. Thirty‐one patients were lost to follow‐up. We report on 180 CML patients with a median age of 38 years (range 9–81). Of these 180 patients, 162 underwent cytogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Although there are many controlled studies in the developed world, there are no reports of studies with long follow up in resource poor setting. We have published 4 articles with regard to response and resistance in our patients with CML [13][14][15][16]. We hypothesize that the survival in our set up is similar to well controlled studies elsewhere.…”
Section: Introductionsupporting
confidence: 67%
“…Although there are many controlled studies in the developed world, there are no reports of studies with long follow up in resource poor setting. We have published 4 articles with regard to response and resistance in our patients with CML [13][14][15][16]. We hypothesize that the survival in our set up is similar to well controlled studies elsewhere.…”
Section: Introductionsupporting
confidence: 67%
“…9 Numerous individual studies have demonstrated the efficacy and safety of GIPAP-facilitated CML treatment in LMICs; however, most care delivery programs have been implemented in private sectors or urban academic centers, with few in sub-Saharan Africa. [10][11][12][13][14] In Rwanda, a CML care delivery program was developed at two rural public hospitals, Rwinkwavu and Butaro Hospitals, in 2009 through collaboration between GIPAP, the Rwanda Ministry of Health (RMOH), the organization Partners In Health (PIH), and advisors from Dana-Farber/Brigham and Women's Cancer Center (DF/BWCC). 15,16 Initially, in-country diagnostic testing was unavailable, and blood and bone marrow specimens were shipped to DF/BWCC for diagnostic confirmation of CML.…”
Section: Introductionmentioning
confidence: 99%